An evaluation of the performance of the Department of Agriculture in Limpopo Province in improving the livelihood of smallholder farmers during the period 1994-2004, with special reference to the Vhembe District - Sitholimela, Silas Ndwakhulu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--University of Stellenbosch, 2007.